Anthracene-Based Zwitterion with a Small HOMO–LUMO Energy Gap - Kayama, Ayane; Shimizu, Akihiro; Shintani, Ryo (Synthesis, 2021)
We have designed and synthesized an anthracene-based zwitterion, 2-methyl-2-azoniaanthracene-7-olate. The zwitterion shows amphoteric redox properties and low-energy-light absorption originating from the small HOMO–LUMO energy gap of ca. 1.7 eV. DFT calculations show that the combination of replacing the C–H with N+–Me and introducing O− is necessary to alter the electronic structure and properties of anthracene significantly.
Keywords: zwitterion; small HOMO–LUMO energy gap; redox; long-wavelength light absorption; negative solvatochromism